Hogar disfuncional y su repercusión en la estabilidad emocional de la personalidad en una mujer de 32 años de edad - Ortiz Potes, Emely Noemi (2023)
This case study has as main objective to examine a dysfunctional home and its influence on the emotional stability of the personality in a 32-year-old female patient, one of the main components of this case is the theoretical support since it comes across important points to understand this case study that are; that it is a dysfunctional home, and everything that involves talking about it, cycles of violence, likewise about emotional stability of the personality, there is also talk about the theory of social learning that will help us to attend to how personality influences through the environment and the psychological processes that were learned during childhood, we also talked about Beck's cognitive model and how he has established the constitution of personality. It should be noted that the method to be used was the qualitative descriptive. The technique that was applied was clinical observation, semi-structured interview, clinical history and some psychometric batteries, likewise diagnostic criteria were used according to the Cie10 that helped us to have a presumptive diagnosis of F60.9 unspecified personality disorder. ., Once this was obtained, the application of Aaron Beck's cognitive behavioral therapy was applied and likewise the therapeutic scheme was carried out, with favorable results for the patient in this case study.